Iδεολογικές αντιπαραθέσεις στα Βαλκάνια. Η προπαγανδιστική χρήση της λατρείας του αγίου Δημητρίου (τέλη 12ου-13ος αι.) - ΟΙΚΟΝΟΜΟΥ Στέλιος (Byzantina Symmeikta, 2019)
St Demetrius, the patron of Thessaloniki through the ages, became the subject of an ideological dispute between the second Bulgarian State and the Byzantine empire (end of 12th c. and throughout the 13th century).The Bulgarians and Vlachs of Haemus attempted to appropriate St Demetrius as the divine protector of their revolt (1185/1186). Τhe Byzantines challenged this founding ideology of the new Bulgarian regime by materialising tsar Ioannitzes’ sudden death in front of Thessaloniki’s walls (1207) and interpreting the Bulgarian king’s end as one of Demetrius’ numerous miracles. According to the author, the Byzantine counter-narrative was not only based on the visualization of St Demetrius’ miraculous intervention in 1207 and the new iconographical type of the martyr on horseback, spearing or unhorsing Ioannitzes, but also on Radomeros’ miraculous murder presumably carried out by the same saint. This later miracle constitutes a conceived historical parallel to Ioannitzes’ death.